Tensile strain-hardening cementitious composites and its practical exploration without reinforcement: A review - Jiang, Fangming; Long, Xiong; Tian, Likang; Tan, Yan; Yu, Jiangtao (Frontiers in Materials, 2022)
Steel is widely used as reinforcement for brittle structural materials such as concrete structure and unreinforced masonry structure (URM). However, the job wasted in steel reinforcement installation and the following corrosion hinder the development of construction industry. The emergence of strain-hardening cement composites (SHCC) provides an opportunity for steel-free construction. This paper provides a comprehensive review of the properties of SHCC and the corresponding practical exploration without reinforcement. The authors herein begin with a discussion on the superior properties of SHCC and its structural applications on the RC structure. Following this, the application of SHCC to retrofit URM is reviewed. Finally, we presents the advances of SHCC used in 3D concrete printing (3DCP) technology , and discuss the feasibility of SHCC structures without reinforcements in the future. When these explorations are coupled with appropriate theoretical models, true values for auto-construction without steel reinforcement will emerge.